2012
DOI: 10.1002/adv.21332
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Oil Absorbency by Using Modified Carbon Nanotubes in Preparation of Oil Sorbents

Abstract: This article reports the first oil-absorbent cross-linked copolymer consisting of modified multiwalled carbon nanotube (MWCNT) and showing high oil absorbency. Also, to investigate and evaluate the effective parameters on oil absorbency, cross-linked dodecyl methacrylate (DDMA)-diphenylacrylamide (DPAA) and DDMA-butyl acrylate (BA) copolymers were synthesized. DDMA was copolymerized with different mol% of DPAA or BA and cross-linked using azobisisobutyronitrile as the initiator and various weight percentages o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…It is well known that organic solvent absorbent gels should have a hydrophobic character to swell in an organic solvent media. In our previous study, MWCNTs were functionalized with acryloyl chloride and 3‐(trimethoxysilyl) propylmethacrylate and was proved that these modified MWCNTs could be applied as an efficient crosslinking agent for the preparation of MWCNT‐based polymeric gels with good three dimensional architectures . Modified MWCNTs in these polymeric absorbents played triple roles simultaneously: as an adsorbent, a comonomer and a crosslinking agent.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is well known that organic solvent absorbent gels should have a hydrophobic character to swell in an organic solvent media. In our previous study, MWCNTs were functionalized with acryloyl chloride and 3‐(trimethoxysilyl) propylmethacrylate and was proved that these modified MWCNTs could be applied as an efficient crosslinking agent for the preparation of MWCNT‐based polymeric gels with good three dimensional architectures . Modified MWCNTs in these polymeric absorbents played triple roles simultaneously: as an adsorbent, a comonomer and a crosslinking agent.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, MWCNTs were functionalized with acryloyl chloride and 3-(trimethoxysilyl) propylmethacrylate and was proved that these modified MWCNTs could be applied as an efficient crosslinking agent for the preparation of MWCNT-based polymeric gels with good three dimensional architectures. [51][52][53] Modified MWCNTs in these polymeric absorbents played triple roles simultaneously: as an adsorbent, a comonomer and a crosslinking agent. We showed that the prepared polymeric absorbents containing CNTs had much higher swelling in oil and some organic solvents than those without CNTs.…”
Section: Preparation Of Il Functionalized Mwcnt-polymeric Gels (Ilmpgs)mentioning
confidence: 99%
See 2 more Smart Citations
“…Even though nanotechnology is not an EOR technique per se, the unique features found at the nanoscale allow the performance of current methods to be improved. The use of nanotechnology in chemical EOR has recently been reported in the form of polymer nano-composites (PNPs or polymer-coated nanoparticles) [3][4][5] and silica nanoparticles [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%